Meningeal metastasis of a malignant peritoneal mesothelioma: A case report and literature review. Issue 12 (2nd December 2019) - Jiang, Yaofei; Mei, Zijie; Cao, Hong; Li, Sirui; Xu, Haibo; Qiu, Hui; Liu, Yu
ABSTRACT: Malignant peritoneal mesothelioma is a very rare tumor originating from the peritoneal serous mesothelium. Meningeal metastasis of malignant peritoneal is even more rare. Here, we reported a case of a 60-year-old female patient with a history of exposure to asbestos for 10 years who presented with massive peritoneal effusion followed by disorder of consciousness and symptoms of cranial nerve injury. The patient was diagnosed as peritoneal mesothelioma with meningeal metastasis through neurological symptoms, cytological finding of cerebrospinal fluid combined with cranial magnetic resonance imaging (MRI). The patient received systemic chemotherapy and total craniospinal irradiation. The follow up visits showed that the survival time of patient after diagnosis of meningeal metastasis from peritoneal mesothelioma was 5 months. To our knowledge, this is the first case of menigeal metastasis of peritoneal mesothelioma. We hope this particular case may be helpful in providing some experience to the treatment of peritoneal mesothelioma with meningeal metastasis.